Strengthening the Moral Intelligence of Students through Character Education, Morality, and Etiquette in Pesantren - Sari, Ririn Eko; Mulyoto, Mulyoto; Mulyo, Mufrod Teguh (Thawalib: Jurnal Kependidikan Islam, 2025)
Weak character education, hostile environments, and family backgrounds influence the moral decline of students. Therefore, pesantren needs to strengthen moral development tangibly and continuously. This study aims to explain the efforts of Pondok Pesantren Nurul Iman Wonogiri to strengthen students' moral intelligence. The research method used is qualitative with a case study approach, utilizing interviews, observations, and documentation as data collection techniques. The research findings show that the pesantren implements character education by combining Salafi and modern methods. Through dialogue, motivation, habituation of worship, and exemplary behavior, the pesantren helps student become more disciplined, religious, and able to control their emotions. Moral education is carried out through the habituation of worship activities such as congregational prayers, dhuha, tahajud, voluntary fasting, and tadarus and tahfidz of the Qur'an, which shape the student's morality. In addition, etiquette education in the pesantren is carried out through curriculum integration, daily activities, pesantren programs, and cooperation with parents. This approach involves exemplarity, spontaneous activities, admonitions, and environmental conditioning. In conclusion, the strategies have successfully formed students with religious, independent, ethical, and noble character gradually and sustainably